2011
DOI: 10.1002/tea.20418
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory materials: Affordances or constraints?

Abstract: Laboratory instruction is critical to the understanding of biology and is a central piece of biological sciences instruction. Although much investigation has focused on the content of biology laboratory exercises, we contend that understanding the extent to which the laboratory materials can aid or limit experimental investigation is of equal importance. In this study, therefore, we investigate the role of timing and availability of laboratory equipment in the context of two different laboratory exercises. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…It is part of the forethought phase, which is the first phase of Zimmerman's () model, namely, the initial understanding of the task and goals before acting on them. Experiences with a less structured environment have been shown to result in greater planning than in structured settings (Jordan, Ruibal‐Villasenor, Hmelo‐Silver, & Etkina, ), endorsing the open‐ended learning environment in our study as appropriate for promoting SRL. Planning in an open‐ended dynamic learning environment is particularly difficult because it requires coping with unknown variables and is characterized by uncertainty about actions’ results (Allen, Hendler, & Tate, ), as in the present study.…”
Section: Self‐reporting Instruments and Promptsmentioning
confidence: 67%
“…It is part of the forethought phase, which is the first phase of Zimmerman's () model, namely, the initial understanding of the task and goals before acting on them. Experiences with a less structured environment have been shown to result in greater planning than in structured settings (Jordan, Ruibal‐Villasenor, Hmelo‐Silver, & Etkina, ), endorsing the open‐ended learning environment in our study as appropriate for promoting SRL. Planning in an open‐ended dynamic learning environment is particularly difficult because it requires coping with unknown variables and is characterized by uncertainty about actions’ results (Allen, Hendler, & Tate, ), as in the present study.…”
Section: Self‐reporting Instruments and Promptsmentioning
confidence: 67%
“…These authors term this a bottom‐up vs. a top‐down perspective. Although the implications of these changes are not known, Jordan et al (2011b) found that when students engage in more top‐down or global discussions about hypothesis testing, their creativity in number of problem solutions generated increased. More data are necessary to draw a similar conclusion between the relationships described in this article.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Toulmin (1972) stated that a scientific discipline includes “a communal tradition of procedures and techniques for dealing with theoretical or practical problems.” Indeed, novices that are new to a discipline are not familiar with the procedures and techniques of the discipline. For example, students' are challenged to comprehend the complex methods that are abundant in adapted primary literature (APL) articles in biotechnology (Falk, Brill, & Yarden, 2008), and novices posed with a typical laboratory task focus on the materials and procedures that are not familiar to them (Jordan, Ruibal‐Villasenor, Hmelo‐Silver, & Etkina, 2011).…”
Section: Knowledge Of Techniques and Procedural Knowledgementioning
confidence: 99%